Effects of online frame-of-reference training on assessment accuracy in the objective structured clinical examination for physical therapy students - Tetsuro Watari; Kei Ohtsuka; Yukari Suzuki; Fumihiro Matsuda; Soichiro Koyama; Naoki Aizu; Yoshikiyo Kanada; Hiroaki Sakurai (Fujita Medical Journal, 2023)
Objectives: This study investigates how online frame-of-reference (FOR) training of raters of the objective structured clinical examination (OSCE) for physical therapy students affects assessment accuracy.